(untitled) (Swiss Medical Weekly, 2010)
Aims: Domestic violence victims are increasingly identified at emergency departments (ED). Studies report a prevalence of 6–30%; women are more frequently affected and to a more serious extent than men. Studies have shown that without screening domestic violence victims are often not recognised. The primary aim of the study is to collect data descriptive of domestic violence victims and to show whether medical documentation meets the requirements of forensic medicine. Methods: Retrospective analysis of medical records using the ED electronic patient database (Qualicare, Qualidoc Bern) at the ED of Bern University Hospital, Inselspital. Demographics, injuries, perpetrators and a semi-quantitative analysis of the medical records have been evaluated for each case. Results: From 1 January 2000 to 31 December 2005, 40 914 women were admitted to the ED. During this time 160 women were identified as victims of domestic violence and met the inclusion criteria for our study. The age ranged from 15–68 years. 63.6% of these women are married or live in a steady relationship. 46% of all victims of domestic violence were treated from Fridays to Sundays. In 70.2% blunt trauma was documented, the head was affected in 49%, 53% showed injuries of only one body area. In 10 cases, strangulation was suspected. 75% of the assaults could be classified as simple assault on the basis of Swiss criminal law. The perpetrator was the husband or partner in 73.4%. 141 cases were included for a semi-quantitative evaluation of the forensic medical documentation. The type of injuries was described in every case, the localisation in 96%, the shape in 26% and the dimensions of the lesions in 36%. Conclusions: The present retrospective assessment of medical reports over a 6-year period shows that domestic violence against female patients was documented in 0.4%. This figure is far below the proportions to be expected from recent data. If these data are to be believed the majority of female victims of domestic violence must have been overlooked at the ED. The implementation of screening for domestic violence seems to be crucial. The types of injury are chiefly the result of superficial, blunt violence, meaning of mild degree from the viewpoint of criminal law. The quality of the forensic documentation is poor and usually insufficient for criminal prosecution. Clinicians require training in the forensic aspects of medical records.